2017
DOI: 10.1109/tste.2016.2608840
|View full text |Cite
|
Sign up to set email alerts
|

Application of Network-Constrained Transactive Control to Electric Vehicle Charging for Secure Grid Operation

Abstract: Abstract-This paper develops a network-constrained trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 21 publications
0
54
0
1
Order By: Relevance
“…Transactive market structure for commercial building HVAC systems [25] Additionally, transactive control has also been applied in the distributed scheduling of EV charging. A network-constrained transactive control paradigm of day-ahead EV charging planning is proposed in [26], [27] for secure distribution network operations. An iterative pricing and scheduling coordination mechanism between the aggregators and DSO is presented in the study so that the day-ahead EV charging demand meets the distribution network constraints.…”
Section: Pilot Projects With Transactive Controlmentioning
confidence: 99%
“…Transactive market structure for commercial building HVAC systems [25] Additionally, transactive control has also been applied in the distributed scheduling of EV charging. A network-constrained transactive control paradigm of day-ahead EV charging planning is proposed in [26], [27] for secure distribution network operations. An iterative pricing and scheduling coordination mechanism between the aggregators and DSO is presented in the study so that the day-ahead EV charging demand meets the distribution network constraints.…”
Section: Pilot Projects With Transactive Controlmentioning
confidence: 99%
“…Other parameter values are not listed for simplicity, but can be accessed by addressing the authors: Note that the control performance of the transactive distribution system was demonstrated in [12]; here the results focus on cost analysis. We show different costs introduced by having negative lambda value and nonnegative lambda value in the transactive distribution system.…”
Section: Case Studiesmentioning
confidence: 99%
“…In this study, we combine the model presented in [7,12] and use the following formulas to characterize the EV charging cost minimization problem:…”
Section: A Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large penetration of intermittent and variable generation introduces operational challenges to the power system. To accommodate the variability of the renewables, it is important to harness the flexibility of the newly introduced units, such as batteries and electric vehicles, especially in the distribution network level [5][6][7]. Enabling this flexibility comes at the cost of an increasingly complex control system, characterized by many state and decision variables [8].…”
Section: Introductionmentioning
confidence: 99%